Evaluación del pavimento de la via rural del sitio San Vicente de el jobo del cantón Arenillas, provincia del Oro - Contento Torres, Rebeca Paulette (Machala : Universidad Técnica de Machala, 2024)
The research evaluated the structural and functional condition of the pavement on the Arenillas – San Vicente del Jobo road through the application of the Pavement Condition Index (PCI), laboratory tests, and the Capacity and Service Manual for Two-Lane Highways (INVIAS). Predominant distresses such as alligator cracking and potholes were identified, affecting pavement integrity. The PCI obtained was 60, classifying the road as "Good," although some segments require intervention. Laboratory tests, including granulometric analysis, moisture content, consistency limits, CBR, and the Marshall test, determined that the pavement structure meets the requirements for light and medium traffic according to the Ministry of Transport and Public Works (MTOP). The capacity and level of service analysis revealed that the road operates at service level E, characterized by unstable traffic flow and low comfort, with a high risk of congestion under minimal traffic disturbances. The evaluation concludes that periodic and corrective maintenance is essential to optimize pavement lifespan and improve road safety. The implementation of standardized methodologies for pavement condition assessment facilitates efficient intervention planning, contributing to the sustainability and functionality of rural road infrastructure.
La investigación evaluó la condición estructural y funcional del pavimento en la vía Arenillas – San Vicente del Jobo mediante la aplicación del Índice de Condición del Pavimento (PCI), ensayos de laboratorio y manual de capacidad y servicio para carreteras de dos carriles (INVIAS). Se identificaron patologías predominantes como piel de cocodrilo y huecos, afectando la integridad del pavimento. El PCI obtenido fue de 60, clasificando la vía en estado "Bueno", aunque con segmentos que requieren intervención. Los ensayos de laboratorio, incluyendo análisis granulométrico, contenido de humedad, límites de consistencia, CBR y ensayo Marshall, determinaron que la estructura del pavimento cumple con los requisitos para tráfico liviano y medio según el Ministerio de Transporte y Obras Públicas (MTOP). El análisis de capacidad y nivel de servicio evidenció que la vía opera en nivel de servicio E, caracterizado por circulación inestable y baja comodidad, con riesgo de congestión ante mínimas perturbaciones del tránsito. La evaluación permite concluir que el mantenimiento periódico y correctivo es fundamental para optimizar la vida útil del pavimento y mejorar la seguridad vial. La implementación de metodologías estandarizadas para la valoración del estado del pavimento facilita la planificación eficiente de intervenciones, contribuyendo a la sostenibilidad y funcionalidad de la infraestructura vial en entornos rurales.
Keywords: EVALUACION,; INDICE DE CONDICION DEL PAVIMENTO; CAPACIDAD; NIVEL DE SERVICIO